Análisis pragmático de los actos de habla directivos en la publicidad Malaya - Mansor, Nor Shahila; Alonso, Emilio Ridruejo (Departamento de Lingüística, Facultad de Filosofía y Humanidades, Universidad de Chile, 2014)
In this article, we use the model of socio-pragmatic to show the pattern of directive speech acts in Malay printed advertisements. Therefore, we will analyze 18 advertisements both institutional and commercial advertising published in 2014 in Malaysia. It is a qualitative analysis based on the Theory of Speech Acts (Searle, 1969). This study reflects the strategies that advertisers apply in the texts to persuade the consumers to change the attitude towards the products offered and these strategies are varied. In these various strategies we found four directive acts that are ‘request’, ‘command’, ‘warning’ and ‘advice’. The tendency of Malay advertisers to use such speech acts in their advertising arguments is not to show rudeness or discourtesy but it is considered as a necessity to bring the attention of potential consumers. However, advertisers tend to reduce the ilocutive effect of directive speech acts with mild expressions in the advertising discourse in order to maintain a good relationship between interlocutors.